The effect of Calcemin drug on bone regeneration in experiment - Khojanov, Iskandar; Shermatov, Gayrat (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article describes results of experimental researches, which were conducted on 40 white laboratory rats at the age of 6 months. Bone regeneration was studied in a perforated transcortical defect, made in the proximal tibial metaphysis, under the effect of Calcemin drug. Unlike other agents, studied before, Calcemin produced a systemic effect on the bone tissue owing to the fact that besides calcium and phosphorus this drug contains microelements, which improve metabolism of normal bones and promote their regeneration. It was found out that Calcemin stimulated reparative osteogenesis and resulted in the formation of bone tissue within the shortest terms.